Embryo rescue and hybridity establishment in hybrid progenies derived from polyemebryonic Citrus species - DUBEY, A K; GUPTA, ANKIT; SHARMA, NIMISHA; SHARMA, R M (The Indian Journal of Agricultural Sciences, 2021)
Due to highly polyemebryonic nature of Rangpur lime and sour orange, development of hybrid is difficult through conventional breeding. Therefore, the present study was carried out at the Division of Fruits & Horticultural Technology, ICAR-Indian Agricultural Research Institute, New Delhi during 2017-19 to improve hybrid seedling recovery among the crosses made between these species. Germination was induced in rescued immature embryos ages (90-100, 110- 120, 130-140, 150-160 and 170-180 days after pollination) on two culture media (MS medium supplemented with 500 mg/l malt extract +1.5 mg/l GA3 + 0.02 mg/l NAA (M1) and DKW medium added with 1.5 mg/l GA3 + 0.02 mg/l NAA (M2). Fruits harvested at younger stage (90-120 DAP) had higher number of functional seeds. Older embryos (>150 days old) germinated earlier on either medium. Embryos rescued at early stage (90-100 DAP), middle age embryos (130-140 DAP) and oldest embryos (170-180 DAP) germinated efficiently (88.85-100%) on M2 medium. The seedling obtained from 170-180 days old embryos grown on M2 medium produced longest primary root and tallest plantlets (7.52 and 4.48 cm) at 60 days after inoculation (DAI). SSR marker analysis revealed that GT03 loci exhibited the polymorphism between male and female parents, proving their ability to detect the hybrids of Rangpur lime (C. limonia) × sour orange (C. aurantium).